2020
DOI: 10.1101/2020.05.31.20118455
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hospital readmissions of discharged patients with COVID-19

Abstract: Background. COVID-19 infection has led to an overwhelming effort by health institutions to meet the high demand for hospital admissions. Aim. To analyse the clinical variables associated with readmission of patients who had previously been discharged after admission for COVID-19. Design and methods. We studied a retrospective cohort of patients with laboratory-confirmed SARS-CoV-2 infection who were admitted and subsequently discharged alive. We then conducted a nested case-control study paired (1:1 ratio) by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 15 publications
(16 reference statements)
0
15
1
Order By: Relevance
“…A study in Switzerland that observed the characteristics of two readmitted patients reported that the patients had coronary artery disease, atrial fibrillation, and aortic stenosis as underlying diseases [29], and a recent study on patients readmitted with COVID-19 to five hospitals in New York City reported that the probability of readmission is higher in patients with hypertension and chronic obstructive pulmonary disease [5]. The finding that the rate of readmission is higher for patients with hypertension as the underlying disease was also confirmed in a study in Spain [19]. In addition, a study on readmitted patients in Wuhan, China reported that patients with pulmonary fibrosis as the underlying disease had a higher risk of readmission [3].…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…A study in Switzerland that observed the characteristics of two readmitted patients reported that the patients had coronary artery disease, atrial fibrillation, and aortic stenosis as underlying diseases [29], and a recent study on patients readmitted with COVID-19 to five hospitals in New York City reported that the probability of readmission is higher in patients with hypertension and chronic obstructive pulmonary disease [5]. The finding that the rate of readmission is higher for patients with hypertension as the underlying disease was also confirmed in a study in Spain [19]. In addition, a study on readmitted patients in Wuhan, China reported that patients with pulmonary fibrosis as the underlying disease had a higher risk of readmission [3].…”
Section: Discussionmentioning
confidence: 69%
“…By gender, men were 1.340 times more likely to be readmitted due to COVID-19 than women. Somani S et al found that out of 103 readmitted patients, 65 were men, two times more than women [5], and a study by Lina Marcela Parra Ramírez et al on COVID-19 readmitted patients showed that more men were readmitted due to COVID-19 [19]. Previous studies found differences in the effects of COVID-19 by gender.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…74 Furthermore, arterial or venous thrombosis accounted for 16.4% of COVID-19 hospital readmissions in a cohort of 1,368 patients likely influencing ischemic conditions in severe cases. 118 Preexisting cardiovascular comorbidities including hypertension and diabetes were associated with COVID-19 case severity, which likely exacerbate heart failure and other cardiac injuries. 4,17,19…”
Section: Thrombosismentioning
confidence: 99%